Systematic review with meta‐analysis: coffee consumption and the risk of cirrhosis. Issue 5 (25th January 2016) - Kennedy, O. J.; Roderick, P.; Buchanan, R.; Fallowfield, J. A.; Hayes, P. C.; Parkes, J.
Summary: Background: Liver cirrhosis is a large burden on global health, causing over one million deaths per year. Observational studies have reported an inverse association between coffee and cirrhosis. Aims: To perform a systematic review and meta‐analysis to characterise the relationship between coffee consumption and cirrhosis. Methods: We searched for studies published until July 2015 that reported odds ratios, relative risks (RR) or hazard ratios for cirrhosis stratified by coffee consumption. We calculated RRs of cirrhosis for an increase in daily coffee consumption of two cups for each study and overall. We performed analyses by study design, type of cirrhosis and mortality. We assessed the risk of bias in each study and the overall quality of evidence for the effect of coffee on cirrhosis. Results: We identified five cohort studies and four case–control studies involving 1990 cases and 432 133 participants. We observed a dose–response in most studies and overall. The pooled RR of cirrhosis for a daily increase in coffee consumption of two cups was 0.56 (95% CI 0.44–0.68; I 2 83.3%). The RR pooled from cohort studies for a daily increase of two cups was 0.58 (95% CI 0.41–0.76; I 2 91.1%) and from case–control studies it was 0.52 (95% CI 0.40–0.63; I 2 0.0%). The pooled RR of alcoholic cirrhosis for a daily increase of two cups was 0.62 (95% CI 0.51–0.73; I 2 0%) and of death from cirrhosis it was 0.55 (95% CI 0.35–0.74; I 2 90.3%). Conclusion: This meta‐analysis suggests that increasing coffee consumption may substantially reduce the risk of cirrhosis.